(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2017)
This paper examined the role of religion in the development of good moral sexual behaviours among University Undergraduates. In Nigeria, sex issues are considered as sacred and usually attached with a myth, however, observations have shown in recent times that these good virtues have been eroded among university undergraduates in Southwest, Nigeria. These category of students now exhibit unwholesome sexual behaviours such as lesbianism, homosexuality, adultery, indecent dressing, masturbation among others and this is considered a serious threat to national development. Therefore, to address this issue, a descriptive research of the survey type was adopted for the study while three hypotheses were tested. The population consisted of all unmarried undergraduates in all the universities in the Southwest geo- political zone of Nigeria. A sample of 1581 respondents which was made up of 750 males and 831 female were selected employing multistage sampling procedure. A simple random sampling technique was used to select three states out of six states in the Southwest, Nigeria. Two universities each were selected through stratified random sampling from Federal, State and Private universities, while 265 students were also selected from each of the universities making a total of 1590. However, 9 students did not filled the questionnaire properly and were therefore rejected remaining 1581 as sample. A self-designed questionnaire titled: Good Moral Sexual Behaviours (GMSB) was used to collect data. The instrument is a 25-items four point- Liker type questionnaire. The findings revealed that religious inclination significantly influenced University undergraduates values and moral sexual behaviours. The study recommended among others that religious organisations should be encouraged to intensify their sermons on acceptable values in terms of moral sexual behaviours to members of their society. University authorities were also advised to come up with appropriate policies to curb the acts of indecent and seductive dressing patterns common among university undergraduates.